Analysis of Implementation of Credit Risk Management in Management Micro Business Financing at PT. Permodalan Nasional Madani Ulamm Balikpapan - Syafri Rinansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze how the implementation of management risks in micro business financing at PT Permodalan Nasional Madani ULaMM Balikpapan so that it can be known the extent of risk management that has been owned company to deal with existing risks. The results of this study indicate that the risk of late installment payments financing until unable to pay off its obligations is a credit risk faced by the company, but the company has prepared risk management In dealing with these risks, there are stages of pre- and post-risk management risks owned by the company in order to face risks that occur or will occur with the aim of minimizing the losses experienced by the company carried out properly in accordance with the standard financing procedures that are owned company, from identifying each risk to controlling it so that every risk that occurs can be overcome by the company